2018
DOI: 10.1111/nph.15510
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of putative chitin deacetylases from Phaeodactylum tricornutum and Thalassiosira pseudonana highlights the potential for distinct chitin‐based metabolic processes in diatoms

Abstract: Summary Chitin is generally considered to be present in centric diatoms but not in pennate species. Many aspects of chitin biosynthetic pathways have not been explored in diatoms. We retrieved chitin metabolic genes from pennate (Phaeodactylum tricornutum) and centric (Thalassiosira pseudonana) diatom genomes. Chitin deacetylase (CDA) genes from each genome (PtCDA and TpCDA) were overexpressed in P. tricornutum. We performed comparative analysis of their sequence structure, phylogeny, transcriptional profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 81 publications
(98 reference statements)
2
28
1
Order By: Relevance
“…It has been suggested that these two elements would quickly disappear from the ocean if chitin stopped circulating [14,15]. To date, chitin metabolism has been investigated in two diatom genera, Thalassiosira and Cyclotella, due to the completion of their genome sequencing [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these two elements would quickly disappear from the ocean if chitin stopped circulating [14,15]. To date, chitin metabolism has been investigated in two diatom genera, Thalassiosira and Cyclotella, due to the completion of their genome sequencing [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate esterase 4 family (CE4) 2 chitin deacetylases (CDAs, EC 3.5.1.41) catalyze the removal of acetyl groups from chitin to form chitosan (1), a polymer of β-(1,4)-linked d -glucosamine residues. CDAs are widely distributed in protists, diatoms, bacteria, fungi, nematodes, and insects (28), playing vital roles in chitinous matrix formation and modification (9), as well as in biological attack of fungal pathogens (5, 10). CDAs have been considered promising targets for the design of antifungal, antibacterial, and pest control reagents (2, 1113).…”
Section: Introductionmentioning
confidence: 99%
“…In fungi and insects, CDAs may play a role in morphogenesis, whereas bacterial CDAs may contribute to chitin degradation for nutritional purposes. Interestingly, CDAs differ in their regioselectivity when acting on chitin oligomers, yielding products with different degrees of acetylation (DAs) and patterns of acetylation (PAs) (4,12,(15)(16)(17)(18)(19)(20)(21)(22). This suggests that both the DA and PA may influence the biological activities of chitosan oligomers and, possibly, polymers (4,23,24).…”
mentioning
confidence: 99%